Therapeutic mechanisms of Lycii Fructus in male infertility: a comprehensive review - Ma, Dongyue; Li, Dexiu; Du, Guanchao; Liu, Shengjing; Wang, Anmin; Chang, Hongyuan; Lv, Hui; Wang, Hao; Wang, Fu; Guo, Jun (Frontiers in Pharmacology, 2025)
BackgroundLycii Fructus (dried goji berry), the dried ripe fruit of Lycium barbarum L., has long been used in traditional Chinese medicine for its functions of tonifying the kidney, nourishing essence, soothing the liver, and improving vision. It has been widely applied to enhance male reproductive function. In recent years, modern pharmacological studies have revealed that Lycii Fructus is rich in various bioactive metabolites, particularly Lycium barbarum polysaccharides, betaine, carotenoids, and flavonoids, which exhibit antioxidant, anti-apoptotic, and hormone-regulating effects. This review aims to systematically summarize existing clinical and mechanistic studies on the protective effects of Lycii Fructus and its key metabolites on male infertility.MethodsA literature survey was conducted on studies reporting the effects of Lycii Fructus and its bioactive metabolites on male reproductive parameters, including spermatogenesis, hormone regulation, testicular structure, and molecular signaling pathways.ResultsEvidence suggests that Lycii Fructus and its metabolites can improve male reproductive function and sperm quality by modulating the hypothalamic–pituitary–gonadal axis, alleviating oxidative stress, inhibiting testicular cell apoptosis, suppressing pro-inflammatory factors, reducing testicular fibrosis, and regulating autophagy. Animal studies have shown that these effects may be mediated through key signaling pathways such as PI3K/Akt, SIRT1/Nrf2, and AMPK/PGC-1α, thereby enhancing testicular steroidogenesis and antioxidant capacity, among other benefits, and mitigating reproductive damage induced by diabetes, obesity, radiation, and environmental toxins. Although clinical evidence supporting the use of Lycii Fructus alone to improve male infertility is still lacking, traditional Chinese medicine compound formulas containing Lycii Fructus have demonstrated good efficacy and safety in treating oligoasthenozoospermia. Given the increasing attention to the safety and preventive health potential of natural botanical medicines, Lycii Fructus is emerging as a promising natural therapeutic agent for the treatment of male infertility.ConclusionLycii Fructus and its metabolites show promising therapeutic potential for male infertility by improving sperm quality, protecting testicular structure and function, and mitigating damage induced by various stressors.